Adopting an active learning approach to teaching in a research-intensive higher education context transformed staff teaching attitudes and behaviours. Issue 3 (3rd May 2016) - White, Paul J.; Larson, Ian; Styles, Kim; Yuriev, Elizabeth; Evans, Darrell R.; Rangachari, P.K.; Short, Jennifer L.; Exintaris, Betty; Malone, Daniel T.; Davie, Briana; Eise, Nicole; Mc Namara, Kevin; et al.
ABSTRACT: The conventional lecture has significant limitations in the higher education context, often leading to a passive learning experience for students. This paper reports a process of transforming teaching and learning with active learning strategies in a research-intensive educational context across a faculty of 45 academic staff and more than 1000 students. A phased approach was used, involving nine staff in a pilot phase during which a common vision and principles were developed. In short, our approach was to mandate a move away from didactic lectures to classes that involved students interacting with content, with each other and with instructors in order to attain domain-specific learning outcomes and generic skills. After refinement, an implementation phase commenced within all first-year subjects, involving 12 staff including three from the pilot group. The staff use of active learning methods in classes increased by sixfold and sevenfold in the pilot and implementation phases, respectively. An analysis of implementation phase exam questions indicated that staff increased their use of questions addressing higher order cognitive skills by 51%. Results of a staff survey indicated that this change in practice was caused by the involvement of staff in the active learning approach. Fifty-six percent of staff respondents indicated that they had maintained constructive alignment as they introduced active learning. After the pilot, only three out of nine staff agreed that they understood what makes for an effective active learning exercise. This rose to seven out of nine staff at the completion of the implementation phase. The development of a common approach with explicit vision and principles and the evaluation and refinement of active learning were effective elements of our transformational change management strategy. Future efforts will focus on ensuring that all staff have the time, skills and pedagogical understanding required to embed constructively aligned active learning within the approach.